Avaliação do programa comportamental em Diabetes Mellitus tipo 2 com mHEALTH: ensaio clínico randomizado - Jéssica Caroline dos santos (2021)
Introduction: Type 2 diabetes mellitus is a chronic condition of high prevalence and the behavioral program with mHealth, with the application of mobile technological resources such as telephone, SMS and WhatsApp, enables the control of the chronic condition. Objective: To evaluate the effects of the behavioral program with mHealth on the modification of psychological attitudes, on the level of empowerment for self-care practices and on metabolic control in type 2 diabetes mellitus. Method: This is a clinical trial with a randomized cluster, carried out with people with type 2 diabetes mellitus, from five Basic Health Units in the East region of the city of Belo Horizonte, Minas Gerais, in the period between 2018 and 2020. The Basic Health Units were clustered and randomized into two analysis groups (intervention: 108; control: 94), totaling 202 participants. The intervention group received the behavioral program with mHealth, consisting of: sending a text message, provided by SMS and WhatsApp resources, and telephone intervention, distributed at initial time (Ti), baseline, with the application of pre-intervention tests ; time 3 (T3), third month with cycle 1; time 6 (T6), sixth month with cycle 2; time 9 (T9), ninth month with cycle 3; and, final time (Tf). The program was based on the behavior change protocol - PMC: 1) problem definition; 2) identification and approach to feelings; 3) goal setting; 4) elaboration of the care plan to achieve the goal(s); and, 5) the person's assessment and experience of the care plan; in the behavioral and psychosocial aspects of living with diabetes; and, in the COMPASSO protocol for phone calls. Thus, in Ti, data was collected on the variables, sociodemographic, clinical, attitudinal, level of empowerment and adherence to self-care practices. At T3, the first cycle of the behavioral program was carried out, 90 text messages were sent via SMS or WhatsApp, or a telephone intervention was carried out with an average duration of 1 hour. In this cycle, the following themes were addressed: problem definition and identification of feelings about diabetes. At T6, three months after T3, the second cycle was carried out, with the sending of 60 text messages and a telephone intervention. In this cycle, all participants in the intervention group received a phone call to develop a care plan and goals for behavior change and, at the end of T6, they received a complementary phone call to strengthen the goals. T9 was performed, the third cycle of intervention, with the same disposition as T6, but with the addition of the step evaluation of the care plan. It is noteworthy that, in the period between intervention cycles, participants received monitoring through text message or telephone call. Finally, in Tf, the final collection of clinical and attitudinal variables, level of empowerment and adherence to self-care practices was carried out. After the final collection, there was a meeting or a call to end the study with feedback of the results to the participants, both for the intervention group and for the control group. For data analysis, we used the Statistical Package for Social Sciences® (SPSS), version 20.0. Descriptive analysis was performed, with the calculation of frequencies and measures of central tendency and dispersion. The Shapiro-Wilk test was applied to verify the normality assumption. For comparisons of means and medians of quantitative variables, Student's t-test and Mann Whitney test were used, respectively. To compare proportions, Pearson's chi-square test or Fisher's exact test was used, and to assess the effect of the intervention, the Wilcoxon test was used to compare medians between the initial and final time. Results: The average age was 62.7 years, with a standard deviation of 9.9 years, 70% are women, 52.4% have a partner, 27.6% do not have primary education and 47.6% declared themselves brown. /yellows. As for clinical variables, it was observed that 52.4% had type 2 diabetes mellitus for more than 10 years. The percentage of those with comorbidities was 96.5%, with hypertension being the most recurrent comorbidity (67.1%). In the intra- and inter-group comparison of questionnaire responses between T1 and T12, it was observed that, in GI, there was a significant change (p<0.05) in psychological attitudes, in the level of empowerment and in adherence to self-care practices, indicating improvement in psychosocial and behavioral variables. In the CG, there was no significant intragroup difference in the variables level of empowerment and adherence to self-care practices. However, there was a significant reduction in the participants' psychological attitudes between T1 and T12. When comparing the intragroup clinical variables, it was found that there was a statistically significant reduction in HbA1c, GME, VLDL, and triglycerides in GI, showing improvement in metabolic and glycemic indices. On the other hand, there was also significant change in HbA1c and GME variables in the CG, but with increased glycemic and reduced attitude score, indicating worsening of participants in this group. The intergroup comparison at T12 indicated that the IG obtained a significant difference (p<0.05) when compared to the CG. Conclusion: The behavioral program with mHealth favored the modification of psychological attitudes, improved level of empowerment, and adherence to self-care practices related to diet and physical exercise in type 2 diabetes mellitus and decreased triglycerides and glycated hemoglobin.